Adopting Agile across borders : a guide to navigating cultural complexity in Agile teams and organizations - Califano, Glaudia; Spinks, David (Apress, 2021)
People are conditioned culturally from an early age, with each of us developing a set of values and behaviors that differ from those in other parts of the world. When adopting Agile, do cultural behaviors and values prevail, or is there a universal "agile culture"? How have people from different cultures adopted Agile to suit them? Are some cultures naturally more suited to adopting Agile than others? Adopting Agile Across Borders answers all of that and more. Teams in all industries are more globally distributed and diverse than ever. Authors Glaudia Califano and David Spinks reveal how people across the world have embraced Agile values alongside their own cultural values, and what this means for the adoption of Agile. In Adopting Agile Across Borders, a rich array of experiences are shared through real-life stories told by members of the global Agile community. Whether you are an Agile practitioner, a product manager, HR personnel, or simply someone interested in leading people more effectively, this book provides essential teamwork insights across the board. Califano and Spinks showcase case studies from around the world to address the opportunities provided by ever greater mobility and advances in technology. Adopting Agile Across Borders is here to ready you for a diverse, more connected future